Pemanfaatan Ekstrak Wortel dan Jambu Biji terhadap Penurunan Hipertensi pada Lansia - Rina Yuli Agita Devi; Frans Ndapajaki; Risca Argadhi Putri (STRADA : Jurnal Ilmiah Kesehatan, 2018)
Hypertension is a disease in someone whose medical condition has an increase in blood pressure above normal. In the elderly the basic mechanism of increasing systolic is in line with the increase in age when there is a decrease in elasticity and stretching in the large arteries. This study aims to find out how to make capsules from carrot and guava extracts and find out the effectiveness of the addition of the extract. The stages of the study included the stage of making optimal extraction using maceration techniques including taking extracts from carrots and guava which were carried out by comparing the number of feeds using 96% ethanol solution and then using the capsule making method. Of the 13 respondents given intervention in the form of herbal therapy for carrot and guava extract with the results of Sistole blood pressure (mmHg) after being given carrot and guava extract.